2018
DOI: 10.1287/mksc.2018.1104
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Last Touch: Attribution in Online Advertising

Abstract: Online advertisers often utilize multiple publishers to deliver ads to multi-homing consumers. These ads often generate externalities and their exposure is uncertain, which impacts advertising effectiveness across publishers. We analytically analyze the inefficiencies created by externalities and uncertainty when information is symmetric between advertisers and publishers, in contrast to most previous research that assumes information asymmetry. Although these inefficiencies cannot be resolved through publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 26 publications
(27 reference statements)
0
20
0
Order By: Relevance
“… 6 See Abhishek, Despotakis, and Ravi (2017) and Berman (2018) for theoretical analyses of multitouch attribution. …”
mentioning
confidence: 99%
“… 6 See Abhishek, Despotakis, and Ravi (2017) and Berman (2018) for theoretical analyses of multitouch attribution. …”
mentioning
confidence: 99%
“…Archak et al (2012) focus on positive spill-over effects. Furthermore, the performance of different advertisers is analysed as well (Berman, 2015). The interactive effects of online and offline activities and their interaction (Naik and Peters, 2009;Wiesel et al, 2011) are well observed and studied.…”
Section: Channel Performancementioning
confidence: 99%
“…For probability models that are typically nonlinear, this lift will be different than when the exposure order is reversed. If we only knew that a consumer was exposed to media 1 and 2 and did not know the order, we would have to cycle through all possible sequences (2 in this case) and assign attribution based on the Shapley (1953) value, as explained in Berman (2017) and Li and Kannan (2014).…”
Section: Proposed Measure For Attributionmentioning
confidence: 99%
“… 3 Note that computing the weights as ratios of increments is similar in spirit to the Shapley Value used in attribution literature (Berman 2017; Li and Kannan 2014). The difference is that we do not have to use permutations over different orders of touchpoints because we observe the exact order of touchpoints. …”
mentioning
confidence: 99%